Circular RNA NF1-419 Inhibits Proliferation and Induces Apoptosis by Regulating Lipid Metabolism in Astroglioma Cells - Li, Ran; Tang, Xiaocui; Xu, Changqiong; Guo, Yinrui; Qi, Longkai; Li, Shan; Ren, Qiuyun; Jie, Wu; Chen, Diling (Recent Patents on Anti-Cancer Drug Discovery, 2022)
Background: Astroglioma is the most common primary tumor of the central nervous system. Currently, there is no effective treatment for astroglioma. In the present study, the extract (L3) from Ganoderma Lucidum (G. lucidum) was found to inhibit the growth of astroglioma U87 cells and change the expression of circular RNAs (circRNAs). One of these, including the circular NF1-419 (circNF1-419), was of interest because NF1 gene is a classic tumor suppressor gene. Objectives: The functional role of circ-NF1-419 in the inhibition of astroglioma cells remains unknown. This study focuses on the role of circNF1-419 in functional abnormalities of U87 astroglioma cells and aims to elaborate on its regulatory mechanism. Methods: The circNF1-419 overexpressing U87 (U87-NF1-419) cells were constructed. We generated U87-NF1-419 to evaluate the role of circNF1-419 on cell cycle, apoptosis, proliferation, tumor growth and metabolic regulation. Finally, we used docking screening to identify compounds in G. lucidum extracts that target circ-419. Results: U87-NF1-419 can promote cell apoptosis and regulate lipid metabolism through glycerophospholipid metabolism and retrograde endocannabinoid signaling. Further examinations revealed that the expression of metabolic regulators, such as L-type voltage-operated calcium channels (L-VOCC), phospholipase C-β3 (PLCβ3), Mucin1, cationic amino acid transporter 4 (CAT4), cationic amino acid transporter 1 (CAT1) and a kinase (PRKA) anchor protein 4 (AKAP4) was inhibited, while phosphatidylserine synthase 1 (PTDSS1) was enhanced in U87-NF1-419 cells. In vivo experiments showed that circNF1-419 inhibits tumor growth in BALB/C nude mice, and enhanced AKAP4 and PTDSS1 in tumor tissues. The virtual docking screening results supported that ganosporeric acid A, ganodermatriol, ganoderic acid B and α-D-Arabinofuranosyladenine in L3 could activate circNF1-419 in astroglioma treatment. Conclusion: This study indicated that circNF1-419 could be a therapeutic target for the clinical treatment of astroglioma. L3 from Ganoderma Lucidum (G. lucidum) could inhibit astroglioma growth by activating circNF1-419.
Keywords: circNF1-419